The Role Of The Police In Overcoming Illegal Mining Of Natural Stones That Impact On Natural Damage And Community Settlement - Roy Moonti; Yusrianto Kadir; Marten Bunga; Yoslan K. Koni; Ramdhan Kasim (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The purpose of this study is how the role of the police in overcoming the illegal mining of natural stone which has an impact on natural damage and community settlements and what factors hinder the police in overcoming the illegal mining of natural stone which has an impact on the natural damage of community settlements. The research method used is the type of research used is empirical normative legal research. Normative law research uses normative legal case studies in the form of legal products, while empirical legal research uses empirical legal case studies in the form of community behavior. The role of the police in overcoming the illegal mining of natural stone that has an impact on natural damage and community settlements in Gorontalo Regency is by conducting outreach to the daenaa village community, then carrying out prevention stages, and finally taking action step by step is not heeded and what factors The factors that hinder the police in overcoming the illegal mining of natural stone that has an impact on natural damage to the settlements of the people of Gorontalo Regency are economic factors, the perpetrators want to avoid the obligations that have been determined, the difficulty factor in obtaining an IUP (Mining Business Permit), the factor of the lack of socialization regarding laws and regulations. invitation and the factor of weak law enforcement.